Chemistry, Pharmacokinetics, Pharmacodynamics and Analytical Methods of Bilastine, a Histamine H1 Receptor Antagonist: An Update - Sharma, Sanjay; Hatware, Ketan; Bhadane, Prashant; Patil, Kiran (Mini Reviews in Medicinal Chemistry, 2021)
Abstract: Bilastine (BIL) is the new generation antihistamine that is used to relieve the symptoms of hayfever, chronic urticaria and other forms of allergic rhinitis. Chemically it is known 2-[4-[2-[4-[1- (2-ethoxyethyl) benzimidazole-2-yl] piperidine-1-yl] ethyl] phenyl]-2-methylpropane acid. The chemical structure of BIL having a hydrophilic carboxylic substituent. BIL has a longer duration of action due to its potent binding affinity to the H1 receptor. This review summarizes the properties, characteristics, chemistry along with analytical and bioanalytical methods used for estimation of BIL from different scientific articles. The literature has demonstrated some methods for quantification of BIL in various sample matrix and pharmaceutical products. Frequently and extensively used antihistaminics are in the clinic practice, a novel, effective, economic and safe analytical methodology is required for routine quality control analysis, bioavailability, and bioequivalence studies. Furthermore, this narrative review summarizes available data on chemistry, pharmacology and analysis of BIL in a different matrix.
Keywords: pharmacodynamics